Life-threatening bleeding of a duodenal gastrointestinal stromal tumor in a teenager: a rare case report - Valli, Piero V.; Valli, Carlo; Pfammatter, Thomas; Bauerfeind, Peter (Endoscopy International Open, 2016)
Duodenal gastrointestinal stromal tumors (GIST) are per se infrequent and are exceptional in children or young adults. So far, only 2 cases of pediatric duodenal GISTs have been published. Here we report on the case of a 19-year-old female patient who was admitted in hemorrhagic shock due to arterial bleeding of a duodenal GIST located in immediate proximity to the major duodenal papilla. After several attempts of endoscopic hemostasis failed, the tumor bleeding was controlled with a second coil embolization of the pancreaticoduodenal arcades.